2020
DOI: 10.29044/v11i1p4
|View full text |Cite
|
Sign up to set email alerts
|

A Research Study into the impact on Emotional Stability of a Transactional Analysis Training Programme intended to develop increased levels of Adult Ego State in Adolescents in Syria

Abstract: A research study is described into the impact on Adult ego state and emotional stability of 36 adolescent students (with 36 in a control group) of a training programme based on transactional analysis concepts run in a school in Damascus. An experimental battery of instruments comprised existing and new instruments including an Ego-State Wheel, an Ego State Problem-Solving Scale, an Ego State Measure, the Emotional Stability Brief Measure, and the Geneva Emotion Wheel. Results showed differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Similar results were reported in a study of the impact of transactional analysis training programs. It found that adolescents who participated in the training program demonstrated better problem-solving strategies, used the Adult ego state more effectively, and expressed more positive feelings compared to their peers [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported in a study of the impact of transactional analysis training programs. It found that adolescents who participated in the training program demonstrated better problem-solving strategies, used the Adult ego state more effectively, and expressed more positive feelings compared to their peers [49].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the present study was to examine functional ego states, life position, and stroke economy, and to disclose patterns of social interaction in adolescents and their parents. Several authors presenting cases from clinical practice indicate the presence of a connection between negative coping strategies, psychological problems, emotional suffering and highly manifested Normative Parent and Adapted Child, as well as the life position "I am not OK" [17,28,49]. At the same time, closeness and good relationships in the family are supported by the giving of positive signs of recognition and lack of stroke economy [26,28].…”
Section: Discussionmentioning
confidence: 99%